Effect of arginine-based deep eutectic solvents on supported porous sorbent for CO2 capture analysis - Nabilah Suhaili,; Lee, Wah Lim,; Lee, Peng Teh,; Siti Nurzubaida Shahdan,; Zaitun Ghazali,; Miyamoto, Manabu,; Uemiya, Shigeyuki,; Rizafizah Othaman, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Carbon dioxide (CO2) as one of the heat-trapping gases, has caused global warming. Being a greener and more economical material, amino acid-based deep eutectic solvents (AADES) have attracted interest in CO2 capture applications. In this paper, the effect of L-arginine (Arg) in binary AADES of arginine-ethylene glycol (Arg-EG) and ternary AADES of choline chloride-ethylene glycol-arginine (ChCl-EG-Arg) on adsorption of CO2 was studied. The solubility, basicity, and physicochemical characteristics were compared with the binary DES (ChCl-EG) before and after being impregnated into a silica gel (SG) via the wet impregnation method. The AADES/SG adsorbents were evaluated for CO2 sorption performance using an automated gas sorption analyzer at 100% CO2 loading and thermogravimetric analysis (TGA) at flue gas conditions (15% CO2/85% N2). Findings show the basicity and the nitrogen content (N%) of AADES/SG were increased as Arg was added and DES/AADES functional group peaks (amino, hydroxyl, alkyl groups) were observed after the impregnation. The CO2 sorption of 16.0 mg/g at 25 °C and 1 atm was achieved by 30% Arg-EG(1:8)/SG followed by 30% ChCl-EG-Arg (1:2:0.1)/SG (14.8 mg/g) and 30% ChCl-EG/SG(1:2) (14.5 mg/g) using an Autosorb iQ2 instruments with 100% CO2 loading. The CO2 uptake was increased almost linearly with increasing pressure and decreased with increasing temperature. The Arg-EG(1:8)/SG shows the highest selectivity toward CO2 than other sorbents with 8.10 mg/g adsorption for 1 h at 15% CO2 loading at 25 °C with higher thermal stability and surface area. Considering environmental, technological, and economic viewpoints, the Arg-EG(1:8)/SG can be explored more as a potential solid sorbent for CO2 capture.